Early Twentieth Century Town Planning Improvements in New Zealand - Petrović, Emina (Architectural History Aotearoa, 2004)
The first decades of the twentieth century were critical for an introduction of town planning views in New Zealand. This was the time when the country was moving in a natural progression from solving the basic problems of establishing new settlements, through extensive infrastructural works (construction of roads and railroads; introduction of electricity and tramways, etc), to the point of early re-evaluations and criticisms of the achieved results. Concurrently the British town planning concepts were, for the first time, discussed among New Zealand architectural professionals and other interested parties as the New Zealand cities and towns were actively being constructed with new and improved infrastructure. This period provided ample opportunity to set up models that could influence future urban developments. This paper will discuss the professional town planning developments in relation to the broader context of urban improvements of the same period. It will explore the concepts that underpinned the developments and evaluate the lasting effects they have had on the development of New Zealand towns and cities.